Salmonella illness outbreaks linked to backyard poultry purchasing during the COVID-19 pandemic: United States, 2020. (27th October 2021) - Nichols, Megin; Gollarza, Lauren; Palacios, Alexandra; Stapleton, G. Sean; Basler, Colin; Hoff, Connor; Low, Mabel; McFadden, Kenai; Koski, Lia; Leeper, Molly; Brandenburg, Joshua; Tolar, Beth
Abstract: Poultry contact is a risk factor for zoonotic transmission of non-typhoidal Salmonella spp. Salmonella illness outbreaks in the United States are identified by PulseNet, the national laboratory network for enteric disease surveillance. During 2020, PulseNet observed a 25% decline in the number of Salmonella clinical isolates uploaded by state and local health departments. However, 1722 outbreak-associated Salmonella illnesses resulting from 12 Salmonella serotypes were linked to contact with privately owned poultry, an increase from all previous years. This report highlights the need for continued efforts to prevent backyard poultry-associated outbreaks of Salmonella as ownership increases in the United States.